Roeping El-Dorado: understanding the architecture behind TVET facilities and how they influence the social context they are located within - Fick, Jay Jonathan (My University, 2021)
This project aims to empower the impoverished community of Eldorado Park by exploring how a Technical Vocational Education and Training (TVET) facility can be designed as an integral contributing part of a larger context. The investigation looks at finding plausable means to encourage education, research and the manufacturing of sustainable products from hemp and other locally sourced materials. The processing and production of raw hemp to the finished product of Hemp-silica bricks and fabrics, would potentially provide opportunities to educate and uplift the practice of industrial hemp production, promoting a viable source of employment opportunities and income to the township of Eldorado park. Research, focusing on hemp properties and potential will be investigated on site, where there will be a scientific based research component to the activities of the compound. The project undertakes an approach which would synchronise both the local community and land upon which it is based. Vernacular architectural typologies are used, where educational buildings are to be investigated along-side that of industrial factory buildings. The architectural response therefore addresses the characteristics and functions of a vernacular building, hinting on industrial style, where exploration of the identities highlighted would overlap, creating a private-public space, exposing educational, research and production fundamentals. This is in relation to programmatic requirements and the physical design of the building, as a response to economic requirements of the community, socio-cultural and general urban context. This thesis is used to form a basis of enquiry into the Vocational Educational System of South Africa, highlighting the development of Hemp-silica education, research and production training. Who we are and where we come from, forms the basis of what arguably is mapped out to be who we will become. By understanding wealth of the self, we understand the complexity that is wealth within the other. Facilitating this process, is mapped out by the events that occur within the social context, where the individual is found, and with this, we then must understand how the relationship acts on both parties. The relationship, goes hand in hand concerning the two spheres of work identified within the South African context, being White-collar work and Blue-collar work. A recognisable trait located in planned townships on the periphery of Johannesburg, South Africa are the effects of an imbalance on educational emphasis placed on the youth residing within these contexts. With low matric pass rates, extremely low employment statistics (60% unemployment in Eldorado Park Township) and an average annual income of R30 000,00.Eldorado Park, is an effervescent layered collection of spaces, occupied by diverse cultural communities, containing different eras of historical experience and stories, each mapped by relationships surrounding a context of grouping and migration, caused by the forced influx and racially dogmatic law, imposed by the Group Areas Act passed 27th April 1950
A design project submitted to the Faculty of Engineering and the Built Environment, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Architecture (Professional) July 2021